Metallogenesis of the Late Palaeozoic Axi–Tawuerbieke Au–Pb–Zn district in the Tulasu Basin, Western Tianshan, China: Constraints from geological characteristics and isotope geochemistry. (28th February 2018) - Peng, Yi‐Wei; Gu, Xue‐Xiang; Cheng, Wen‐Bin; Zhao, Xiao‐Bo; Wang, Guan‐Nan; Lu, Liang‐Tao; Han, Jian‐Min
Abstract : The Tulasu Basin is an important epithermal gold ore cluster situated in the Boluokenu Polymetallic Belt, Western Tianshan, China. The Axi Au, Tabei Pb–Zn, and Tawuerbieke Au deposits in this basin represent different types of epithermal mineralization. These are products of the same tectonic‐magmatic‐hydrothermal event, related to the southward subduction of the North Tianshan Ocean beneath the Yili‐Central Tianshan Plate during the Late Devonian to Early Carboniferous. The spatial relationships, preservation levels, and evolution of the three deposits are still debated. Hence, systematic geological field investigations, ore microscopy, and isotopic analyses were carried out on these three deposits. The S–Pb–C–H–O isotopic compositions indicate that the ore‐forming components were derived from the volcanic‐subvolcanic rocks, as well as from circulating meteoric waters. The occurrence of adularia, silicified platy carbonates, and quartz characterized by crustiform/colloform/colloidal textures at Axi indicate that boiling was the main precipitation mechanism for the Au mineralization. The Pb–Zn ores from Tabei are characterized by abundant banded coarse‐grained quartz crystals with dog tooth and comb textures, suggesting that the sulphides precipitated slowly due to conductive cooling. The Tawuerbieke Au deposit is characterized by pervasive silicification and phyllic alteration accompanying veinlet and disseminated ore, which formed via metasomatic water–rock interaction. According to the ore textures, intrusion sizes, and mineral assemblages, it can be inferred that all three deposits experienced different extents of erosion (Axi < Tabei < Tawuerbieke) and that there is exploration potential for concealed porphyry Cu–Au mineralization. Exploration should focus on deep targets beneath the Tawuerbieke Au deposit.